Islamic Religious Education Curriculum as a Pillar of Islamic Character Formation for Students - Jihan Fira Aziza; Juliani; Pitri Ramawati; Pranata Seju Surbakti; Muhammad Reza Fahlevi (Journal of Contemporary Islamic Primary Education, 2024)
This study aims to analyze the role of the Islamic Religious Education (PAI) curriculum as a fundamental pillar in shaping students' Islamic character in the era of globalization. Utilizing a library research method, data were collected from various academic literature sources, including scholarly journals, books, and official documents published within the last five years. The findings indicate that the PAI curriculum significantly contributes to the internalization of moral, social, and spiritual values among students. Strategies such as project-based learning, extracurricular activities, and the reinforcement of Islamic values have proven effective in shaping students’ Islamic character. However, the implementation of this curriculum faces challenges, including limited resources, inadequate teacher training, and insufficient time allocation for Islamic character education. The study concludes that the development of an adaptive PAI curriculum is essential to meet contemporary needs, integrating technology and value-based approaches. Furthermore, this research provides practical implications, emphasizing the need for innovative teaching methods, continuous teacher training, and supportive policies to ensure the effectiveness of the PAI curriculum in fostering a generation with strong Islamic character, capable of navigating modern challenges.